THE ROLE OF MUNICIPAL GOVERNANCE IN THE INNOVATIVE REVITALIZATION OF REGIONAL BUSINESS PROCESSES AND THE DEVELOPMENT OF INTELLECTUAL CAPITAL - Kramarenko, Iryna; Nadtochii, Iryna; Hryshyna, Nataliya; Archybisova, Dariia; Irtyshchev, Oleksandr (Public Management and Policy, 2026)
This article examines the role of municipal governance in the innovative revitalization of regional business processes and the development of intellectual potential. The dynamics of the renewal and development of regional business structures are analyzed. The main factors hindering the renewal of regional business structures are identified, including: a lack of funding and investment support; nearly 84% of business entities in Ukraine are individual entrepreneurs who lack sufficient resources to join business associations; the largest share of scientific personnel works for the government, while the business sector has more resources but fewer highly qualified personnel; the lack of transparent mechanisms to protect the rights of investors in large integrated structures deters partners from establishing joint ventures. Research has shown that the content of regional strategies and their implementation plans differ significantly from one another, yet they are all aimed at strengthening and developing the regions. It has been determined that the role of municipal government in shaping development strategies is crucial and should be focused on ensuring the well-being of the local population through programs that promote sustainable socioeconomic growth. It has been demonstrated that a significant portion of regions possess intellectual potential which, with the support of local municipalities and international funding, can develop development programs and tools. The analysis revealed that a significant portion of the intellectual potential of the scientific workforce is concentrated in the regions but is not being fully utilized, as evidenced by statistical disparities. It was emphasized that at the regional level, it is necessary to develop appropriate strategies, programs, and plans for development and recovery with the involvement of scientific personnel, the expert community, and business representatives, which will contribute to the formation of well-founded management decisions and the improvement of the effectiveness of regional policy.